2015
DOI: 10.1094/pdis-07-14-0672-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Pseudomonas savastanoi Causing Bacterial Leaf Spot of Mandevilla sanderi in Slovenia

Abstract: Foliar necrotic spots with narrow chlorotic halos were observed on different cultivars of Brazilian Jasmine (Mandevilla sanderi) during spring 2010 in several commercial greenhouses in Slovenia. Up to 70% were symptomatic and were unmarketable. No galls were observed on the stems of symptomatic plants. Circular, flat, granulated colonies with entire margins were isolated from symptomatic leaves of two plants from different greenhouses on King's B medium (KB). The isolates were negative for levan, oxidase, pect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…However, cross-pathogenicity tests performed in olive and oleander could not confidently classify the isolates as members of any of these two pathovars (Eltlbany et al 2012). Although partial sequencing of the rpoD gene from two Slovenian isolates showed a closer proximity to Psn strains (Pirc et al 2015), results from pathogenicity tests in oleander plants were not reported.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…However, cross-pathogenicity tests performed in olive and oleander could not confidently classify the isolates as members of any of these two pathovars (Eltlbany et al 2012). Although partial sequencing of the rpoD gene from two Slovenian isolates showed a closer proximity to Psn strains (Pirc et al 2015), results from pathogenicity tests in oleander plants were not reported.…”
Section: Introductionmentioning
confidence: 91%
“…This emergent disease is caused by the most prevalent bacterial pathogen of dipladenia, Pseudomonas savastanoi. The first report of this disease dates back to 2010 in the USA (Putnam et al 2010), with European outbreaks occurring over the following years in France, Germany (Eltlbany et al 2012), Slovenia (Pirc et al 2015) and Spain (Caballo-Ponce and Ramos 2016). With Spain and Italy as the main producers of dipladenia in Europe, this emergent disease has also become a serious concern for European growers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the host range of Psr isolates is restricted to Spanish broom (Janse, 1982; Iacobellis et al, 1998; Ramos et al, 2012). Knot formation by P. savastanoi has also been described in several other hosts, including jasmine (Gardan et al, 1992b), privet (Gardan et al, 1992b), mock privet (Gardan et al, 1992b), forsythia (Bradbury, 1986), buckthorn (Temsah et al, 2007a), fontanesia (Mirik et al, 2011), pomegranate (Bozkurt et al, 2014), myrtle (Goumas et al, 2000; Temsah et al, 2007b; Cinelli et al, 2014) and dipladenia (Putnam et al, 2010; Eltlbany et al, 2012; Pirc et al, 2014; Caballo-Ponce and Ramos, 2016) ( Table 1 ). Although these P. savastanoi hosts are classified in several plant families, over 50% of them belong to the Oleaceae family.…”
Section: Tumorigenic Pathovars Of P Savastanoimentioning
confidence: 99%